2019
DOI: 10.18632/oncotarget.27259
|View full text |Cite
|
Sign up to set email alerts
|

The multikinase inhibitor RXDX-105 is effective against neuroblastomain vitroandin vivo

Abstract: Neuroblastoma is the most common extracranial solid tumor of childhood and accounts for 15% of all pediatric cancer-related deaths. New therapies are needed to improve outcomes for children with high-risk and relapsed tumors. Inhibitors of the RET kinase and the RAS-MAPK pathway have previously been shown to be effective against neuroblastoma, suggesting that combined inhibition may have increased efficacy. RXDX-105 is a small molecule inhibitor of multiple kinases, including the RET and BRAF kinases. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In parallel, Zhang et al [59] characterized the effect of another RET inhibitor, cabozantinib (XL184), on in vitro and in vivo neuroblastoma paradigms. Subsequent studies from the same group found comparable results when using the small-molecule RET/ multikinase inhibitor RXDX-105 [60] or the RET/multikinase inhibitor regorafenib (BAY 73-4506) [61]. Notably, the effect of regorafenib on in vitro and in vivo neuroblastoma models had been previously reported by Chen et al [62].…”
Section: Retmentioning
confidence: 64%
“…In parallel, Zhang et al [59] characterized the effect of another RET inhibitor, cabozantinib (XL184), on in vitro and in vivo neuroblastoma paradigms. Subsequent studies from the same group found comparable results when using the small-molecule RET/ multikinase inhibitor RXDX-105 [60] or the RET/multikinase inhibitor regorafenib (BAY 73-4506) [61]. Notably, the effect of regorafenib on in vitro and in vivo neuroblastoma models had been previously reported by Chen et al [62].…”
Section: Retmentioning
confidence: 64%
“…Continuous live-cell imaging was performed as previously described. 31 Briefly, neuroblastoma cells were plated in 96-well plates at seeding densities between 10,000 and 25,000 cells/well and treated with regorafenib alone and in combination with 13- cis -retinoic acid as above. The plates were placed into the IncuCyte ® Zoom TM continuous live-cell imaging system (Essen Bioscience, Ann Arbor, MI), and phase-contrast images were taken every 6 h at 10Ă— magnification for 72 h. Cell confluence was calculated using IncuCyte ® analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…The human neuroblastoma cell lines (SK-N-AS; SK-N-BE(2); SK-N-SH; SH-SY5Y; IMR-32; SH-EP) used in this study have been previously utilized by our laboratory (45)(46)(47) and were purchased from American Type Culture Collection (ATCC, www.atcc.org) or were generously provided by Susan Cohn (The University of Chicago Children's Hospital, Chicago, IL) or John Maris (Children's Hospital of Philadelphia, Philadelphia, PA). HEK 293T cells were purchased from ATCC.…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%